Imagination of history in Stevan Sremac's Short stories from antique books - Rajović Dragana R. (Baština, 2022)
The subject of this paper are historical stories of Stevan Sremac. Their artistic value lags behind the value of his realistic prose. Bearing in mind the style of the writer's historical narratives, it is concluded that the writer's primary motive in writing was "national-educational action" and not literary creativity. Following the trail of legends and traditions, the author neglected historical facts, which resulted in artistic inconclusiveness. Stevan Sremac tried to balance historical facts with artistic vision and legends.